CRIMINAL ACTS OF ABUSE OF TRANSPORTATION APPLICATIONS ONLINE IN SURABAYA - Septian, Gery Kiven Agung (Universitas Islam Lamongan, 2023)
Online transportation is a development in the world of transportation and communication which is inseparable from the development of science and technology which is increasingly advanced and very sophisticated. This study aims to find out the forms of abuse of online transportation applications, to find out the efforts of the police in preventing criminal acts of violating online transportation applications and to find out the penalties for online transportation drivers in the crime of theft of online transportation applications, and to find out the factors inhibiting the police in prevent criminal acts of theft of online transportation applications. Based on the results of the research it is known that the provisions regarding criminal acts of electronic fines are specifically regulated in Article 30 paragraph (3) of Law Number 19 of 2016 concerning Information and Electronic Transactions (UU ITE). The criminal threat of this article is stated in Article 46 paragraph (3) of the ITE Law, which is imprisonment for a maximum of 8 (eight) years.